ՌԴ քաղաքակրթական նույնականացման հիմնախնդիրն արտաքին քաղաքականությունում - Վարդազարյան Մարութ (YSU Journal of International Affairs, 2016)
In the current complex geopolitical processes the civilizational identification of the Russian Federation is highlighted. It will contribute to the consolidation of the government and the society and will simplify the overcoming of the challenges that the country faces. In terms of foreign policy, the civilizational identification assumes the selection of the development vector of the country, the formation of a new image in the current international arena, as well as the assurance of sovereignty and national security. Russia is neither Europe nor Asia nor Eurasia, but simply Russia, which at the same time is a unique civilization. Only in this way it can preserve its historical individuality and through cooperation with other civilizations it can continue to stay as an important factor of the world civilization.